46. ISSUES OF POPULIST POWER IN SOCIAL LIFE - Salimov Bakhriddin Lutfullaevich. Umarbekov Bunyod Saidullaevich (Innovative technologies in construction Scientific Journal, 2023)
The article analyzes the fact that Immanuel Kant put forward the idea of populist power in social relations, the content of this idea is that the legislative power should only express the will of the people, and this will of the people should be the source of laws in a legal state.